Discovery of variation in genes related to agronomic traits by sequencing the genome of Cucurbita pepo varieties - C. Pérez-Moro; D. D’Esposito; C. Capuozzo; A. Guadagno; A. Pérez-de-Castro; M. R. Ercolano (BMC Genomics)
Abstract Background Cucurbita pepo L. cultivars display high morphological traits variation. In addition, C. pepo faces numerous threats, such as viral and fungal infections, which significantly influence crop cultivation. Recent genomic advancements improved the understanding of genetic diversity and stress responses in this crop. We investigated genetic variations related to plant morphology and quality traits. Additionally, the inclusion of both powdery mildew (PM) and Zucchini yellow mosaic virus (ZYMV) susceptible and tolerant varieties facilitated the examination of genetic diversity concerning biotic stress. Results The sequencing of eight Cucurbita pepo varieties produced an average of 40 million raw reads with a coverage of reference genome ranging from 22 to 40X. More than 4.7 million genomic variants were identified in all genomes. Based on admixture and PCA analysis, the eight C. pepo genotypes were grouped in two clusters belonging to Cocozelle and Zucchini groups, with “Whitaker” separated from the rest of the accessions. Genes involved in pathways related to gibberellin regulation, leaf development, and pigment accumulation resulted highly affected by variation suggesting that the diversity observed among varieties in plant and fruit morphology could be related to variants identified in such genes. Each variety showed its own set of genetic differences. The genomic comparison of 381e, 968Rb and SPQ allowed the identification of variants in chromosome regions affecting response to Zucchini yellow mosaic virus (ZYMV) and powdery mildew (PM). Variants in key genes associated with resistant traits were identified, suggesting potential pathways and mechanisms involved in biotic stress response and plant immunity. Conclusions Genetic variations affecting morphology and fruit quality in C. pepo emphasize their significance for breeding efforts. Furthermore, the genomic comparison of 381e, 968Rb and SPQ highlighted variants in chromosomal regions influencing zucchini’s response to PM and ZYMV. These findings could pave the way for more targeted and effective genetic improvement strategies, thereby potentially leading to increased agricultural productivity and quality.